Adipose-Derived Mesenchymal Stem Cell Exosomes Suppress Hepatocellular Carcinoma Growth in a Rat Model: Apparent Diffusion Coefficient, Natural Killer T-Cell Responses, and Histopathological Features - Sheung-Fat Ko; Hon-Kan Yip; Yen-Yi Zhen; Chen-Chang Lee; Chia-Chang Lee; Chung-Cheng Huang; Shu-Hang Ng; Jui-Wei Lin (Hindawi Limited, 2015)
We sought to evaluate the effects of adipose-derived mesenchymal stem cells (ADMSCs) exosomes on hepatocellular carcinoma (HCC) in rats using apparent diffusion coefficient (ADC), natural killer T-cell (NKT-cell) responses, and histopathological features. ADMSC-derived exosomes appeared as nanoparticles (30-90 nm) on electron microscopy and were positive for CD63, tumor susceptibility gene-101, and β-catenin on western blotting. The control (n=8) and exosome-treated (n=8) rats with N1S1-induced HCC underwent baseline and posttreatment day 10 and day 20 magnetic resonance imaging and measurement of ADC. Magnetic resonance imaging showed rapidly enlarged HCCs with low ADCs in the controls. The exosome-treated rats showed partial but nonsignificant tumor reduction, and significant ADC and ADC ratio increases on day 10. On day 20, the exosome-treated rats harbored significantly smaller tumors and volume ratios, higher ADC and ADC ratios, more circulating and intratumoral NKT-cells, and low-grade HCC (P<0.05 for all comparisons) compared to the controls. The ADC and volume ratios exhibited significant inverse correlations (P<0.001, R2=0.679). ADMSC-derived exosomes promoted NKT-cell antitumor responses in rats, thereby facilitating HCC suppression, early ADC increase, and low-grade tumor differentiation. ADC may be an early biomarker of treatment response.